2018
DOI: 10.3389/fpsyg.2018.01646
|View full text |Cite|
|
Sign up to set email alerts
|

Creative Arts-Based Therapies for Stroke Survivors: A Qualitative Systematic Review

Abstract: Background: Stroke is a life-threating cerebrovascular disease. Without proper and immediate treatment, it can cause long-term disabilities and even death. While current rehabilitation focuses on functional needs, it does not fully address the psychosocial issues. Creative arts-based therapies, however, may have the potential to be of assistance.Methods: A systematic review was conducted to synthesize the qualitative findings of the stroke survivors' positive and negative experiences in participating in creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 30 publications
(133 reference statements)
1
23
0
1
Order By: Relevance
“…Esta situación presupone que las personas con ingresos y niveles educativos bajos resulten menos beneficiadas para acceder a recursos y con menos posibilidad para gozar de buena salud. Esta situación podría influenciar la prevalencia de la ecv y la discapacidad, más aún cuando "a nivel mundial existe un desafío creciente relacionado con el número de personas que sobreviven a una ecv y que a largo plazo conducirá a un aumento de personas con discapacidad" [26].…”
Section: Discussionunclassified
“…Esta situación presupone que las personas con ingresos y niveles educativos bajos resulten menos beneficiadas para acceder a recursos y con menos posibilidad para gozar de buena salud. Esta situación podría influenciar la prevalencia de la ecv y la discapacidad, más aún cuando "a nivel mundial existe un desafío creciente relacionado con el número de personas que sobreviven a una ecv y que a largo plazo conducirá a un aumento de personas con discapacidad" [26].…”
Section: Discussionunclassified
“…The evidence summarised above suggests that there is a need for more holistic rehabilitation programmes, especially non-pharmacological and non-invasive modalities, to address the psychosocial needs and improve the quality of life of stroke survivors. 12 Arts-based programmes (such as 'Stroke Odysseys (SO)' discussed below) are one such approach that shows promising results in enhancing the well-being, self-esteem, social life and rehabilitation experiences of patients with stroke. 13 Indeed, over the past decade, several studies conducted in this patient population have consistently shown a positive impact of different art modalities on psychological (eg, enhancement in confidence and a better sense of control), social (eg, increased social interactions and peer support) and functional (eg, improvement in physical abilities) outcomes.…”
Section: Open Accessmentioning
confidence: 99%
“…13 Indeed, over the past decade, several studies conducted in this patient population have consistently shown a positive impact of different art modalities on psychological (eg, enhancement in confidence and a better sense of control), social (eg, increased social interactions and peer support) and functional (eg, improvement in physical abilities) outcomes. 12 Nonetheless, despite the growing body of research on the benefits of art interventions, the process of scaling-up these interventions, embedding them into healthcare and its associated challenges are not yet well established. Preliminary data indicate that SO (discussed below) is received positively by those who take part, 14 however, identifying barriers to implementation and exploring ways to overcome these obstacles are essential to successfully and sustainably embed SO into clinical pathways and roll out the programme at a wider scale.…”
Section: Open Accessmentioning
confidence: 99%
“…Young stroke survivors (< 65 years old) are more likely to suffer to a greater extent than their older counterparts because of their longer overall survival time. They often report unmet psychosocial-spiritual needs [ 7 , 10 , 12 18 ]. To help young stroke survivors address their unique psychosocial-spiritual concerns, which have been found to be crucial for rehabilitation adherence and achieving favourable recovery outcomes [ 11 , 19 ], there is a need for a holistic rehabilitation programme, particularly the non-pharmacological one, as an adjuvant to conventional physical and occupational rehabilitation to buffer against mental health issues, reduce psychosocial stress, resume social connections, and re-instill hope [ 6 , 8 , 20 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The non-verbal communication and symbolic expression through art media during the art-making process can further enhance engagement and help express feelings or thoughts that are difficult to verbalize. An expressive arts-based intervention is uniquely equipped to take advantage of utilising all art modalities, such as visual art, music, dance/movement, drama, and writing [ 33 ], to address the psychosocial-spiritual needs of stroke survivors [ 18 ]. Nevertheless, systematic research on its effectiveness is still limited, including on young survivors [ 27 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%